2020
DOI: 10.1177/0020764020935489
|View full text |Cite
|
Sign up to set email alerts
|

Increased stressful impact among general population in mainland China amid the COVID-19 pandemic: A nationwide cross-sectional study conducted after Wuhan city’s travel ban was lifted

Abstract: Objectives: Our study aimed to determine the impact of the COVID-19 pandemic on psychological responses and lifestyle changes among the general population in mainland China following the re-opening of the Wuhan city. Methods: A cross-sectional survey was conducted in April 2020. Participants of Chinese nationality aged ⩾ 18 years were asked to complete a modified validated Chinese version of a questionnaire regarding the impact of event scale (IES), family and social support, mental health–related lifestyle ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 13 publications
(30 reference statements)
5
54
1
2
Order By: Relevance
“…According to our study, 68.4% of the participants with the IES score ≥26 showed a moderate-tosevere stressful impact, which was much higher than our previous studies (Ma et al 2020;Zhang and Ma 2020a). In addition, in our study, females were reported to more likely experience psychological impact caused by the COVID-19 pandemic than males.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…According to our study, 68.4% of the participants with the IES score ≥26 showed a moderate-tosevere stressful impact, which was much higher than our previous studies (Ma et al 2020;Zhang and Ma 2020a). In addition, in our study, females were reported to more likely experience psychological impact caused by the COVID-19 pandemic than males.…”
Section: Discussioncontrasting
confidence: 51%
“…Additionally, participants also were asked to complete six validated and modified questions with a Cronbach's alpha of 0.88, which were used to indicate the changes of stress from work and family, financial pressure, panic feeling, anxiety and helplessness due to the COVID-19 pandemic (answer options: much decreased, decreased, unchanged, increased and much increased) (Ma et al 2020;Zhang and Ma 2020a).…”
Section: Impact Of Event Scale (Ies)mentioning
confidence: 99%
See 2 more Smart Citations
“…The World Health Organization (WHO) recorded >8400 cases of SARS and 800 deaths worldwide (Zhong et al 2003). The COVID-19 outbreak has also led to serious consequences including unprecedented levels of infection and deaths, decreased quality of life, and increased stress due to strict lockdowns and limits on social interactions (Cao et al 2020;Ma et al 2020;Zhang and Ma 2020a,b). In mainland China, the number of diagnosed patients from 21st January 2020 until 2nd February 2020 increased from 330 cases to 17,000 cases within two weeks (Dong et al 2020).…”
Section: Introductionmentioning
confidence: 99%